2019
DOI: 10.29322/ijsrp.9.02.2019.p8616
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Climate Factors Influencing Dengue Incidences in Colombo, Sri Lanka: Poisson and Negative Binomial Regression Approach

Abstract: Dengue fever is a mosquito-borne disease caused by the dengue virus. Transmission of the virus depends on the presence of Aedes mosquito. Dengue has become a global problem and is common in more than a hundred countries. It is most prevalent in tropical and subtropical regions. It has been a major public health challenge in Sri Lanka in recent years. Mosquito generation and the spread of dengue are known to be influenced by the climate. Identifying the climate factors that affect dengue outbreaks would be help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Their work showed that, based on cross-correlations, dengue incidence had the most significant associations with maximum monthly temperature, minimum monthly temperature, relative humidity, and rainfall, at a lag of two months. Chandrakantha [9] also identified that rainfall data within a two-month lag period were a significant predictor in dengue incidences in Colombo, Sri Lanka. Their work was based on Poisson and negative binomial regression modeling.…”
Section: Introductionmentioning
confidence: 92%
“…Their work showed that, based on cross-correlations, dengue incidence had the most significant associations with maximum monthly temperature, minimum monthly temperature, relative humidity, and rainfall, at a lag of two months. Chandrakantha [9] also identified that rainfall data within a two-month lag period were a significant predictor in dengue incidences in Colombo, Sri Lanka. Their work was based on Poisson and negative binomial regression modeling.…”
Section: Introductionmentioning
confidence: 92%
“…Identifying the association between dengue incidents and meteorological factors is also useful for the development of dengue warning systems, and hence, the administration can set out the dengue control measures promptly. A recent study (Chandrakantha, 2019) shows how climatological factors affecting the spread of dengue in the city of Colombo, Sri Lanka over the period from 2010 to 2018 using the Poisson and negative binomial regression approach. The study didn't consider the time lag and has been analysed in small geographical areas.…”
Section: Open Access Articlementioning
confidence: 99%